Necesidad jurídica de reformar el artículo 110 numeral 11 del código civil, en cuanto al abandono como causal de divorcio. - Valle Cuenca, Luis Anival (2015)
This research addresses a legal problem of deep social resonance, as two great institutions on which the civil law develops are family and property. Both are the basis of civilized coexistence, of human relationships. Ecuadorian law family law mainly regulates the legal consequences of marriage. Family life and social relationship establishes rights and duties between people, as guaranteed by the different standards of ethical, religious, civic, usual, economic, etc. producing rights and obligations subject to legal and procedural standards, the legal protection for the State and its specialized institutions. In this research the legal issues under Article 110 clause 11 of the Ecuadorian Civil Code, in divorce on the grounds of unjustified abandonment uninterrupted addressed. Meanwhile, the civil law of Ecuador determined from one of the causes that can end the marriage; divorce. Section 110 Section 11, subsection 1 and 2 of the Civil Code states: "The voluntary and unjustified abandonment of the other spouse, for over a year without interruption. However, if you neglect to in the preceding paragraph, any lasted more than three years, may be sued for divorce by either spouse. " Divorce on the grounds set out in Article 110, paragraph 11, the statement constitution expressly contravenes Article 67: "The family is recognized in its various forms. The State shall protect the fundamental unit of society and ensure conditions that promote the full attainment of its purposes. This work is corroborated by conducting a field study regarding the problem to investigate, to what has been obtained the judgment of a group of lawyers in free practice using the techniques of survey and interview those who have expressed their views and opinions regarding the proposed theme. The study with the drawing of conclusions, recommendations and the proposed amendment to the Civil Code is also supplemented.